Fireproof cable for subway
By combining a variety of materials and flame retardants in the outer sheath of the subway cable, a gradient capacity-enhancing network and ceramic skeleton are formed, which solves the problem of insufficient fire resistance performance of subway cables in fire, and achieves high fire resistance and low smoke heat release effect.
Patent Information
- Application Number
- CN202510279155.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-11
AI Technical Summary
Subway cables are difficult to meet the requirements of high fire protection levels when a fire occurs, and the heat and smoke generated during combustion threaten the safety of passengers' lives.
A fire-resistant cable for subway is adopted. The outer sheath is composed of PVC resin, nylon 66 resin, aliphatic TPU, EVA-G-MAH, POE-G-MAH and other materials, and DOPO derivatives and silicone resin are added to coat zirconium phosphate particles as flame retardant to form a gradient capacitance network and ceramic skeleton to improve fire resistance.
It significantly improves the fire-proof and flame-retardant performance of the cable, has a high flame-retardant grade, and has a small amount of heat and smoke production after combustion, ensuring passenger safety.
Smart Images

Figure CN119798888A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cables, in particular to a fireproof cable for subways. Background Art
[0002] With the rapid development of urban rail transit, subways, as a large-capacity public transportation tool, can significantly reduce the use of private cars, thereby reducing carbon emissions and air pollution. They can also effectively transport a large number of passengers and reduce traffic congestion on the road. However, subway tunnels are closed and crowded. Once a fire occurs, it will seriously threaten the safety of passengers. Therefore, laws and regulations have put forward higher requirements for the fire resistance of subway cables. How to further improve the fire resistance level of subway cables and reduce the heat and smoke generated during combustion has become the current research focus. Summary of the invention
[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes a fire-resistant cable for subways.
[0004] The technical solutions adopted are as follows: A fireproof cable for subway, comprising a plurality of cable cores and a PET film layer for fixing the plurality of cable cores; The PET film layer is sequentially coated with a mica tape wrapping layer, a copper mesh shielding layer and an outer sheath; The outer sheath is made of the following raw materials in parts by weight: 50-60 parts of PVC resin, 8-15 parts of nylon 66 resin, 5-10 parts of aliphatic TPU, 5-8 parts of EVA-G-MAH, 3-5 parts of POE-G-MAH, 1-3 parts of calcium zinc stabilizer, 10-20 parts of filler, 1-2 parts of polyethylene wax, 0.5-1 parts of calcium stearate, 10-20 parts of flame retardant, 10-30 parts of plasticizer, 0.1-0.5 parts of antioxidant; The flame retardant consists of DOPO derivatives and organosilicon resin-coated zirconium phosphate particles.
[0005] Furthermore, the mass ratio of the DOPO derivative to the silicone resin coated zirconium phosphate particles is 1-5:1-5.
[0006] Furthermore, the structural formula of the DOPO derivative is as follows: .
[0007] Furthermore, the preparation method of the DOPO derivative is as follows: 4,4',4''-methylenetriphenol reacts with 2,2-dihydroxymethylpropionic acid to obtain intermediate 1, intermediate 1 reacts with epichlorohydrin to obtain intermediate 2, and intermediate 2 finally reacts with DOPO to obtain the DOPO derivative.
[0008] Furthermore, the preparation method of the silicone resin coated zirconium phosphate particles is as follows: Zirconium phosphate is modified with tetramethylammonium hydroxide and KH-550 in sequence to obtain premodified zirconium phosphate, PDMS is mixed with n-hexane, an organic tin catalyst is added to obtain a prepolymer solution, the premodified zirconium phosphate is dispersed in the prepolymer solution, the temperature is raised to reflux after ultrasonic dispersion, the reaction is stirred for 1-10 hours, and then ethyl orthosilicate is added, and the reaction is continued for 1-10 hours.
[0009] Furthermore, the preparation method of the silicone resin coated zirconium phosphate particles is as follows: Zirconium oxychloride octahydrate is mixed with phosphoric acid, and a sealed hydrothermal reaction is carried out at 180-200°C for 12-48h. After the reaction is completed, the precipitate is collected, washed, and dried to obtain zirconium phosphate. The zirconium phosphate is dispersed in DMSO, and tetramethylammonium hydroxide is added. The precipitate is collected after stirring for 1-10h, washed, dried, and then dispersed in KH-550 hydrolyzate, stirred at 60-80°C for 1-5h, and the precipitate is collected. The precipitate is washed and dried to obtain premodified zirconium phosphate. PDMS is mixed with n-hexane, and an organic tin catalyst is added to obtain a prepolymer solution. The premodified zirconium phosphate is dispersed in the prepolymer solution, and the temperature is raised to reflux after ultrasonic dispersion. After stirring for 1-10h, ethyl orthosilicate is added, and the reaction is continued for 1-10h.
[0010] Furthermore, the filler consists of calcium carbonate and calcined kaolin in a mass ratio of 1-5:1-5.
[0011] Furthermore, the plasticizer is at least one of epoxidized soybean oil, dioctyl phthalate, and dioctyl terephthalate.
[0012] Furthermore, the antioxidant is antioxidant 1010 and / or antioxidant 168.
[0013] Furthermore, the cable core consists of a conductor and a cross-linked polyethylene inner sheath.
[0014] It has the following beneficial effects: The invention provides a fireproof cable for subway, wherein the PVC resin in the outer sheath is a matrix material, and the nylon 66 resin has high tensile strength, rigidity and heat resistance, and can greatly increase the mechanical properties of the PVC resin after being added, but due to the difference in polarity, the two are not compatible, and the invention forms a gradient capacity expansion network by adding EVA-G-MAH and POE-G-MAH double grafting system, wherein the maleic anhydride group contained can form a chemical bond with the amino group of the nylon 66 resin, and at the same time, its main chain is compatible with the polar structure of PVC, and a transition layer can be formed at the interface of PVC and nylon, thereby enhancing the interface bonding force, reducing phase separation, and improving the mechanical properties, and the aliphatic TPU has good compatibility with the PVC resin, is dispersed in the PVC matrix, can absorb impact energy through an "island structure", prevent crack propagation under the action of external force, and improve the mechanical strength of the outer sheath, and can also reduce the melt viscosity of the PVC resin and the nylon 66 resin, broaden the processing temperature window, improve the blending fluidity, and reduce the risk of thermal decomposition; DOPO derivatives can decompose to generate phosphorus-containing free radicals at high temperatures. These free radicals can capture active free radicals such as H· and HO· generated during the combustion process, thereby interrupting the combustion chain reaction and slowing down the spread of flames. The triphenyl structure increases the carbon content and can decompose to form a denser carbon layer covering the cable surface, which plays a role in physical isolation and reducing smoke density. The hyperbranched epoxy structure improves the dispersibility and compatibility of DOPO derivatives in the resin matrix, avoiding the degradation of mechanical properties caused by the addition of DOPO derivatives. Zirconium phosphate, as a typical layered compound, can not only play a role in strengthening and toughening, but also play the role of inorganic flame retardant with its high heat resistance, high barrier and self-extinguishing properties. The silicone resin coating not only improves the dispersibility of zirconium phosphate and avoids agglomeration, but also the decomposition products of the silicone resin react with the decomposition products of zirconium phosphate to form phosphorus silicon glass, which together construct a ceramic skeleton to form a continuous and dense ceramic layer, isolating oxygen, delaying combustion, and reducing the release of heat, smoke or toxic gases. The outer sheath granules prepared by the present invention have excellent mechanical properties and extremely good fire retardant properties, not only have a high flame retardant grade, but also generate little heat and smoke after combustion, and are excellent materials for preparing fireproof cables for subways. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a schematic diagram of the structure of the fireproof cable for subway in Example 1, in which the reference numerals represent: 1-Copper conductor, 2-cross-linked polyethylene inner sheath, 3-PET film layer, 4-mica tape wrapping layer, 5-copper mesh shielding layer, 6-outer sheath.
[0016] Figure 2 This is the synthetic route of the DOPO derivative in Example 1. DETAILED DESCRIPTION
[0017] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0018] PVC resin: TL-1000, Tianjin LG Dagu Chemical Co., Ltd.; Nylon 66 resin: 20NSP NC, Ascend, USA; Aliphatic TPU: WHT-1190, Wanhua Chemical; EVA-G-MAH: SG-MAH-1003, Nanjing Julong Technology; POE-G-MAH: FB521A, Jiayirong Polymer (Shanghai) Co., Ltd.; Calcium zinc stabilizer: CEZ-T™ 8100, Baerlocher, Germany; Calcium carbonate: CC-2000, Jiangxi Guangyuan Chemical; Calcined kaolin: LK-800, Fujian Longyan Kaolin Company; Polyethylene wax: JRF-200, Shanghai Kumho Sunny; Calcium stearate: DZ-202, Qingdao Deda Zhicheng Chemical; Flame retardant: homemade; Plasticizer DOTP: Palatinol® DOTP, BASF, Germany; Antioxidant 1010: JY-1010, Beijing Jiyi New Materials.
[0019] Embodiment 1: A fireproof cable for subway, comprising four cable cores and a PET film layer 3 for fixing the four cable cores; The cable core consists of a copper conductor 1 and a cross-linked polyethylene inner sheath 2; The PET film layer is sequentially coated with a mica tape wrapping layer 4, a copper mesh shielding layer 5 and an outer sheath 6; The outer sheath 6 is made of the following raw materials in parts by weight: 55 parts of PVC resin, 12 parts of nylon 66 resin, 8 parts of aliphatic TPU, 6 parts of EVA-G-MAH, 4 parts of POE-G-MAH, 2 parts of calcium zinc stabilizer, 10 parts of calcium carbonate, 10 parts of calcined kaolin, 1.5 parts of polyethylene wax, 0.5 parts of calcium stearate, 15 parts of flame retardant, 20 parts of plasticizer DOTP, and 0.25 parts of antioxidant 1010; The flame retardant is composed of DOPO derivatives and silicone resin-coated zirconium phosphate particles in a mass ratio of 1:2.
[0020] The structural formula of DOPO derivatives is as follows: .
[0021] The preparation method of DOPO derivatives is as follows: Under nitrogen protection, 4,4',4''-methylenetriphenol (0.1 mol), 2,2-dihydroxymethylpropionic acid (0.3 mol) and catalyst p-toluenesulfonic acid (1 g) were added to a flask, and the mixture was stirred and heated to 140°C for reaction for 5 h. During the reaction, the water generated by the reaction was separated by a water separator. After the reaction, the nitrogen was stopped, and a vacuum pump was connected to perform reduced pressure distillation until no water was distilled out. The mixture was cooled to room temperature, dissolved in an appropriate amount of acetone, recrystallized in toluene, and filtered to obtain intermediate 1. Under nitrogen protection, intermediate 1 (0.01 mol) and epichlorohydrin (0.08 mol) were added to a flask, and the mixture was stirred and heated to 110°C, and 4.5 g of sodium hydroxide was added to continue the reaction for 1. h and then cooled to room temperature, 100 ml of dichloromethane and 100 ml of deionized water were added, the dichloromethane phase was separated after sufficient stirring, dried over anhydrous sodium sulfate and concentrated under reduced pressure to obtain intermediate 2. Under nitrogen protection, DOPO (15 mmol) was added to the flask, heated until dissolved, and then intermediate 2 (5 mmol) was added. The reaction was stirred and kept warm for 10 h and then returned to room temperature to obtain the DOPO derivative. ESI-MS (m / z) (M + ): Theoretical value 1625.59, measured value 1625.13, synthesis route see Figure 2 .
[0022] The preparation method of silicone resin coated zirconium phosphate particles is as follows: 100g of zirconium oxychloride octahydrate was mixed with 1000ml of 12mol / L phosphoric acid, and then poured into a hydrothermal reactor containing a polytetrafluoroethylene liner, sealed and heated to 200℃ for hydrothermal reaction for 48h. After the reaction, the precipitate was collected, washed with deionized water until neutral, vacuum dried, and ground to obtain zirconium phosphate. 30g of zirconium phosphate was added to 100ml of DMSO, stirred under ultrasound for 30min to disperse, and then 15g of tetramethylammonium hydroxide was added. After stirring at room temperature for 1h, the precipitate was collected and washed with deionized water and vacuum dried. KH-550, anhydrous ethanol and deionized water were mixed in a mass ratio of 2:7.2:0.8, and stirred at 50℃ for 30min to obtain a KH-550 hydrolyzate. The dried zirconium phosphate was added to the KH-550 hydrolyzate in a mass ratio of 1:10, stirred at 70℃ for 2h, cooled to room temperature and filtered, and the precipitate was washed with deionized water and vacuum dried to obtain a pre-modified zirconium phosphate. 50g PDMS was mixed with 500 ml of n-hexane, 0.1 g of dibutyltin dilaurate was added as a catalyst, and the reaction was stirred for 30 min to obtain a prepolymer solution. 25 g of pre-modified zirconium phosphate was added to the prepolymer solution, and the mixture was ultrasonically dispersed for 30 min, then the temperature was raised to reflux, and the reaction was stirred for 5 h. Then 5 g of ethyl orthosilicate was added, and the reaction was continued for 1 h. The mixture was restored to room temperature, filtered, and the precipitate was collected and washed with deionized water and anhydrous ethanol, and then vacuum dried to obtain silicone resin-coated zirconium phosphate particles.
[0023] The preparation method of the outer sheath granules is as follows: The raw materials were placed in a high-speed mixer, mixed at 65°C for 10 minutes, and then transferred to a twin-screw extruder. The extrusion was performed at a main engine speed of 80 r / min and a temperature of 150-170°C to obtain outer sheath pellets.
[0024] Embodiment 2: A fireproof cable for subway, comprising four cable cores and a PET film layer 3 for fixing the four cable cores; The cable core consists of a copper conductor 1 and a cross-linked polyethylene inner sheath 2; The PET film layer is sequentially coated with a mica tape wrapping layer 4, a copper mesh shielding layer 5 and an outer sheath 6; The outer sheath 6 is made of the following raw materials in parts by weight: 60 parts of PVC resin, 15 parts of nylon 66 resin, 10 parts of aliphatic TPU, 8 parts of EVA-G-MAH, 5 parts of POE-G-MAH, 3 parts of calcium zinc stabilizer, 10 parts of calcium carbonate, 10 parts of calcined kaolin, 2 parts of polyethylene wax, 1 part of calcium stearate, 15 parts of flame retardant, 30 parts of plasticizer DOTP, 0.5 parts of antioxidant 1010; The flame retardant is composed of DOPO derivatives and silicone resin-coated zirconium phosphate particles in a mass ratio of 1:2.
[0025] The structure and preparation method of DOPO derivatives are the same as those in Example 1; The preparation method of silicone resin coated zirconium phosphate particles is the same as that of Example 1; The preparation method of the outer sheath granules is as follows: The raw materials were placed in a high-speed mixer, mixed at 65°C for 10 minutes, and then transferred to a twin-screw extruder. The extrusion was performed at a main engine speed of 80 r / min and a temperature of 150-170°C to obtain outer sheath pellets.
[0026] Embodiment 3: A fireproof cable for subway, comprising four cable cores and a PET film layer 3 for fixing the four cable cores; The cable core consists of a copper conductor 1 and a cross-linked polyethylene inner sheath 2; The PET film layer is sequentially coated with a mica tape wrapping layer 4, a copper mesh shielding layer 5 and an outer sheath 6; The outer sheath 6 is made of the following raw materials in parts by weight: 50 parts of PVC resin, 8 parts of nylon 66 resin, 5 parts of aliphatic TPU, 5 parts of EVA-G-MAH, 3 parts of POE-G-MAH, 1 part of calcium zinc stabilizer, 10 parts of calcium carbonate, 10 parts of calcined kaolin, 1 part of polyethylene wax, 0.5 parts of calcium stearate, 15 parts of flame retardant, 10 parts of plasticizer DOTP, 0.1 parts of antioxidant 1010; The flame retardant is composed of DOPO derivatives and silicone resin-coated zirconium phosphate particles in a mass ratio of 1:2.
[0027] The structure and preparation method of DOPO derivatives are the same as those in Example 1; The preparation method of silicone resin coated zirconium phosphate particles is the same as that of Example 1; The preparation method of the outer sheath granules is as follows: The raw materials were placed in a high-speed mixer, mixed at 65°C for 10 minutes, and then transferred to a twin-screw extruder. The extrusion was performed at a main engine speed of 80 r / min and a temperature of 150-170°C to obtain outer sheath pellets.
[0028] Comparative Example 1: It is basically the same as Example 1, except that nylon 66 resin is not added to the raw material of the outer sheath 6.
[0029] Comparative Example 2: It is basically the same as Example 1, except that aliphatic TPU is not added to the raw material of the outer sheath 6.
[0030] Comparative Example 3: It is basically the same as Example 1, except that EVA-G-MAH is not added to the raw material of the outer sheath 6.
[0031] Comparative Example 4: The method is basically the same as Example 1, except that POE-G-MAH is not added to the raw material of the outer sheath 6.
[0032] Comparative Example 5: The method is basically the same as Example 1, except that no DOPO derivative is added to the flame retardant.
[0033] Comparative Example 6: The method is basically the same as Example 1, except that no silicone resin-coated zirconium phosphate particles are added to the flame retardant.
[0034] Comparative Example 7: The method is basically the same as Example 1, except that commercially available zirconium phosphate (purchased from Fujian Ruisen New Materials Co., Ltd.) is used to coat the zirconium phosphate particles instead of the silicone resin.
[0035] Performance Testing The outer sheath granules in Examples 1-3 of the present invention and Comparative Examples 1-7 were made into test pieces for performance testing.
[0036] The tensile strength is tested in accordance with the provisions of GB / T 1040.3-2006 “Determination of tensile properties of plastics Part 3 Test conditions for films and sheets”, the specimen is type 5, and the tensile rate is 100 mm / min.
[0037] Limiting oxygen index (LOI) test: Tested on an oxygen index tester according to ASTM D2863-77 standard, the size of the sample is 100mm×6.5mm×3mm.
[0038] The ISO5660-1 standard test sample is used to test the changes in heat release and smoke release over time during combustion. The radiation power is 50kW, the size of the sample is 100mm×100mm×3mm, and the total heat release (THR) and total smoke release (TSP) are measured.
[0039] The test results are shown in Table 1 below: Table 1:
[0040] It can be seen from Table 1 above that the outer sheath granules prepared by the present invention have excellent mechanical properties and extremely good fire retardant properties. Not only does it have a high flame retardant grade, but it also produces little heat and smoke after combustion. It is an excellent material for preparing fireproof cables for subways.
[0041] By comparing Example 1 with Comparative Examples 1-4, it can be seen that the addition of nylon 66 resin, aliphatic TPU, EVA-G-MAH and POE-G-MAH plays a positive role in improving the mechanical properties of the outer sheath; By comparing Example 1 with Comparative Examples 5-6, it can be seen that the addition of DOPO derivatives and silicone resin-coated zirconium phosphate particles plays a positive role in improving the fire retardant properties of the outer sheath; By comparing Example 1 with Comparative Example 7, it can be seen that compared with commercially available zirconium phosphate, the silicone resin-coated zirconium phosphate particles prepared in the present invention have a greater improvement in the fire retardant performance of the outer sheath.
[0042] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A fireproof cable for subway, characterized in that: It comprises a plurality of cable cores and a PET film layer for fixing the plurality of cable cores; The PET film layer is sequentially coated with a mica tape wrapping layer, a copper mesh shielding layer and an outer sheath; The outer sheath is made of the following raw materials in parts by weight: 50-60 parts of PVC resin, 8-15 parts of nylon 66 resin, 5-10 parts of aliphatic TPU, 5-8 parts of EVA-G-MAH, 3-5 parts of POE-G-MAH, 1-3 parts of calcium zinc stabilizer, 10-20 parts of filler, 1-2 parts of polyethylene wax, 0.5-1 parts of calcium stearate, 10-20 parts of flame retardant, 10-30 parts of plasticizer, 0.1-0.5 parts of antioxidant; The flame retardant consists of DOPO derivatives and organosilicon resin-coated zirconium phosphate particles.
2. The fireproof cable for subway according to claim 1, characterized in that: The mass ratio of the DOPO derivative to the silicone resin-coated zirconium phosphate particles is 1-5:1-5.
3. The fireproof cable for subway according to claim 1, characterized in that: The structural formula of the DOPO derivative is as follows: 。 4. The fireproof cable for subway according to claim 3, characterized in that: The preparation method of the DOPO derivative is as follows: 4,4',4''-methylenetriphenol reacts with 2,2-dihydroxymethylpropionic acid to obtain intermediate 1, intermediate 1 reacts with epichlorohydrin to obtain intermediate 2, and intermediate 2 finally reacts with DOPO to obtain the DOPO derivative.
5. The fireproof cable for subway according to claim 1, characterized in that: The preparation method of the silicone resin-coated zirconium phosphate particles is as follows: Zirconium phosphate is modified with tetramethylammonium hydroxide and KH-550 in sequence to obtain premodified zirconium phosphate, PDMS is mixed with n-hexane, an organic tin catalyst is added to obtain a prepolymer solution, the premodified zirconium phosphate is dispersed in the prepolymer solution, the temperature is raised to reflux after ultrasonic dispersion, the reaction is stirred for 1-10 hours, and then ethyl orthosilicate is added, and the reaction is continued for 1-10 hours.
6. The fireproof cable for subway according to claim 5, characterized in that: The preparation method of the silicone resin-coated zirconium phosphate particles is as follows: Zirconium oxychloride octahydrate is mixed with phosphoric acid, and a sealed hydrothermal reaction is carried out at 180-200°C for 12-48h. After the reaction is completed, the precipitate is collected, washed, and dried to obtain zirconium phosphate. The zirconium phosphate is dispersed in DMSO, and tetramethylammonium hydroxide is added. The precipitate is collected after stirring for 1-10h, washed, dried, and then dispersed in KH-550 hydrolyzate, stirred at 60-80°C for 1-5h, and the precipitate is collected. The precipitate is washed and dried to obtain premodified zirconium phosphate. PDMS is mixed with n-hexane, and an organic tin catalyst is added to obtain a prepolymer solution. The premodified zirconium phosphate is dispersed in the prepolymer solution, and the temperature is raised to reflux after ultrasonic dispersion. After stirring for 1-10h, ethyl orthosilicate is added, and the reaction is continued for 1-10h.
7. The fireproof cable for subway according to claim 1, characterized in that: The filler consists of calcium carbonate and calcined kaolin in a mass ratio of 1-5:1-5.
8. The fireproof cable for subway according to claim 1, characterized in that: The plasticizer is at least one of epoxidized soybean oil, dioctyl phthalate and dioctyl terephthalate.
9. The fireproof cable for subway according to claim 1, characterized in that: The antioxidant is antioxidant 1010 and / or antioxidant 168.
10. The fireproof cable for subway according to claim 1, characterized in that: The cable core consists of a conductor and a cross-linked polyethylene inner sheath.
Citation Information
Patent Citations
Intrinsic flame-retardant cable head flash-sealing coating and preparation method thereof
CN111171704A
Phosphorus-containing compound, epoxy resin composition, molding compound product, preparation method and application
CN111777641A
Powder coating with high salt spray corrosion resistance and preparation method thereof
CN113637394A
Fireproof and moistureproof subway cable and preparation method thereof
CN113773591A
Crosslinked polyethylene heat-resistant insulated cable
CN115512887A
Cited By
Low-temperature-resistant anti-ultraviolet multilayer insulating blanket and preparation method thereof
CN120534037A
High-performance anti-interference fireproof cable and preparation method thereof
CN121394011A